1994
DOI: 10.1111/j.1440-1827.1994.tb01725.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary plasmacytoma of the thyroid: A case report and comparative literature study between Western nations and Japan

Abstract: A 52 year old man presented with primary thyroid plasmacytoma. The patient was initially followed up for thyroid dysfunction. The histological examination of the removed thyroid revealed a proliferation of mature and immature plasma cells indicative of plasmacytoma with Hashimoto's disease. After radiotherapy (40 Gy) to the neck following right hemi-thyroidectomy, the patient is currently alive and well 3 years after diagnosis without any evidence of tumor. The immunohistological examination of the removed thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The electronic searches yielded 1143 articles (PubMed: 418, Web of Science: 292, Embase: 265, and Scopus: 168) and 82 studies reporting 102 individuals were included in this systematic review 17–98 (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electronic searches yielded 1143 articles (PubMed: 418, Web of Science: 292, Embase: 265, and Scopus: 168) and 82 studies reporting 102 individuals were included in this systematic review 17–98 (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…A recent systematic review identified concordance rates higher than 64% for the smear and 77% for the cell‐block technique regarding diagnostic capability for the evaluation of intraosseous jaw lesions, including malignant lesions 16 . Despite several published reports on the cytopathological diagnosis of PCN, either in isolated manifestations (extramedullary or solitary bone plasmacytoma) or as a consequence of PCM, 17–98 there is a lack of compiled information investigating the agreement of cytopathological and histopathological findings, along with others ancillary cytological methods such as smears and cell blocks. In fact, FNAC represents a faster, cheaper and more diversified noninvasive diagnostic approach.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical features of both conditions are quite similar, often accompanied by autoimmune thyroiditis 2,7,8 and by immunoglobulin abnormalities in the serum. 2,7,9,10 The pathogenesis of both conditions may involve excessive thyroid stimulation that contributes to uncontrolled B-cell replication leading to tumor formation. 2,7 The unique features of this case is that three patterns of protein electrophoreses, i.e., normal, the appearance of monoclonal immunoglobulins, and their disappearance after a total thyroidectomy, were consecutively recorded over 6 years.…”
Section: Discussionmentioning
confidence: 99%
“…2,7,9,10 The pathogenesis of both conditions may involve excessive thyroid stimulation that contributes to uncontrolled B-cell replication leading to tumor formation. 2,7 The unique features of this case is that three patterns of protein electrophoreses, i.e., normal, the appearance of monoclonal immunoglobulins, and their disappearance after a total thyroidectomy, were consecutively recorded over 6 years. In contrast, most reported cases involve the coexistence of immunoglobulin abnormalities in the serum and plasmacytoma of the thyroid at the time of diagnosis 8,9 or the presence of monoclonal immunoglobulins at the time of MALT neoplasm diagnosis and their disappearance after thyroidectomy.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] In their effort to summarize the literature on thyroid plasma cell neoplasms in 1994, Kovacs et al [ 1 ] collated 50 cases of solitary EMP of the thyroid and 16 cases of thyroid involvement with systemic multiple myeloma. In a similar effort, but including the Japanese literature, Ohshima et al [ 8 ] identified 34 cases of solitary thyroid EMP in the Western literature and further 32 cases in the Japanese literature. Since then, further 19 cases of solitary EMP of the thyroid [ Table 1 ] and 11 cases of thyroid EMP with multiple myeloma [ Table 2 ] have been reported as case reports in the English literature.…”
Section: Discussionmentioning
confidence: 99%